DIGITAL MARKETING AS BUSINESS PERFORMANCE DETERMINANT MEDIATED BY CUSTOMER RELATIONSHIP MANAGEMENT (CRM) IN CREATIVE INDUSTRIES OF MICRO BUSINESS IN THE 4.0 INDUSTRIAL REVOLUTION ERA IN INDONESIA - Hadiyati, Ernani; Mulyono, Sugeng; Gunadi, Gunadi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Small Medium Entreprise (SMEs) contribute not only to the improvement of job vacancy and decrease poverty, but they also serve as the source of growth for export and gross domestic product (GDB). The development of industrial revolution reaches to the 4.0 industrial era. The Trade Ministry’s Strategy of Making Indonesia 4.0 illustrates the trend and strategy of Indonesian SMEs in involving in the 4.0 Industry so that they can be competitive among other countries. To know and analyze the influences of digital marketing towards business performance that is mediated by customer relation management (CRM). It was qualitative one research. The research population was SMEs of creative industries producing batik crafts as excellent products in Bangkalan dan Pamekasan towns, East Java Province, Indonesia. Sample consisted of seventy (70) Small Medium Entreprise (SMEs). Sample was taken with proportional random sampling and purposive sampling. Data collection used questionnaire. Data were analyzed with Structural Equation Modeling (SEM) PLS. The result of model test of the digital-marketing influences towards business performance with the mediation of Customer Relationship Management (CRM). Implication the research result can be recommended as the consideration for the central and local governments in the empowering program for SMEs in the creative industry; and it can the consideration for SMEs in managing their business.